Global mapping of physical activity promotion strategies in Fibromyalgia- A comprehensive methodological scoping review protocol - Saumya Srivastava; Aishwarya Nair; Dhanesh Kumar K U; Rakesh Krishna Kovela; Vaishali K; Ashwani Verma; Mukesh Kumar Sinha (MethodsX)
Fibromyalgia Syndrome (FMS) is a chronic, broad, diffuse, and non-inflammatory musculoskeletal condition. Several studies were conducted on the effects of physical activity (PA) and strategies to promote it in people with FMS. The resulting scoping review will provide an analysis of the strategies being researched and executed. This study outlines the protocol for a scoping review to collect, analyse and compile the promotion strategies for PA in FMS. The proposed protocol will be guided by Arksey and O'Malley's framework and advanced methodology study by Levac et al. The search method will comprise of terms pertaining to FMS, PA, and its promotion. To ascertain relevant studies, predetermined inclusion and exclusion criteria will be used. Studies included must be performed on FMS patients with PA as the intervention with an outcome related to quality of life, pain, and fatigue. Data extraction of the included studies will be done through three investigators using Rayyan software. Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) will be used to describe the study